Opinions of Al-Raghib Al-Isfahani's linguistic (502 AH) in his book "Vocabulary of the Words of the Qur’an" (Analytical study) (Journal of the College of Basic Education, 2022)
In this research, I have tried to present some of his views in which he expressed his opinion purely, grammatically and rhetorically, knowing that I traced the vocabulary in which I found his views according to his authorship method, which is authorship on alphabets, starting from Hamza to Ya. It is noticeable that he was different in terms of presenting his views on the current issues, so we find him once more in depth during the presentation of the item, as it gives a complete opinion, but sometimes he omits aspects of it, but rather he suffices with partial references. The study came out with some results, and it seems that he benefited from basing his linguistic opinions from sources that worked to refine his opinion, which are Quranic readings, poetic evidence, and Arab speech. And singled out some of his views on the level of private application in the word (Ma), although he did not reveal a new science, but his uniqueness is due to the nature of the Quranic term that he studied in its context. It can be said: It was descriptive, from the phonemic level to the rhetorical methods of use.